2005
DOI: 10.1200/jco.2005.01.9950
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine in Combination With Alemtuzumab Is Effective and Feasible in Patients With Relapsed or Refractory B-Cell Chronic Lymphocytic Leukemia: Results of a Phase II Trial

Abstract: The new FluCam regimen is effective and feasible in patients with relapsed and refractory B-CLL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
105
0
5

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(120 citation statements)
references
References 35 publications
10
105
0
5
Order By: Relevance
“…The T-cell population gradually recovered to baseline levels by 36 weeks after therapy initiation [30]. Similar results on the recovery of CD4 + cells in alemtuzumab combination therapy were reported [12]. Importantly, several studies have shown that infectious events typically occur around the time of T-cell and neutrophil nadirs (Fig.…”
Section: Effect Of Alemtuzumab On Immune Cellssupporting
confidence: 79%
See 2 more Smart Citations
“…The T-cell population gradually recovered to baseline levels by 36 weeks after therapy initiation [30]. Similar results on the recovery of CD4 + cells in alemtuzumab combination therapy were reported [12]. Importantly, several studies have shown that infectious events typically occur around the time of T-cell and neutrophil nadirs (Fig.…”
Section: Effect Of Alemtuzumab On Immune Cellssupporting
confidence: 79%
“…In a recent study, 36 [12]. Most infections occurred within the first 3 months of treatment, when CD4 + cells were at the lowest levels ( Table 2).…”
Section: Alemtuzumab In Combination Therapymentioning
confidence: 88%
See 1 more Smart Citation
“…Efficacy did not vary significantly between genetic subgroups, indicating that alemtuzumab treatment could overcome the adverse prognostic impact of IGHV mutation status, TP53 mutation, and genomic aberrations. The potential benefit of alemtuzumab in combination with chemotherapy was first observed in 6 patients by Kennedy et al [57]; their findings were confirmed by a phase II trial on relapsed or refractory CLL, which reported an OR of 83%, including 11 patients with CR, and resolution of disease in all affected sites [58].…”
Section: Clanahan Et Al Treatment Of Chronic Lymphocytic Leukemiasupporting
confidence: 51%
“…In a phase II trial 36 patients were included. A high overall response rate was reached with 83 % (11 CR, 19 PR), but there were remarkable adverse events: fungal pneumonia in two progressive patients and one case of death caused by E. coli sepsis at CMV reactivation [17].…”
Section: Alemtuzumabmentioning
confidence: 93%